The Role of Parents in Improving Students' Religious Attitudes - Yuliana, Resma; Nurjanah, Ida (Jurnal Paradigma, 2021)
The religious attitudes of students today have a negative tendency, including a lack of discipline in performing prayers, lazy to read al-Qur’an and refuting the words of older people. This is influenced by the family environment, community environment, and school environment. As for what was being studied by researchers at MI Ma'arif Cekok Ponorogo found that the problem of students’s religious attitudes apart from being influenced by the above there are also other factors, there is peer interaction and lack of attention and affection from their parents, because most of the children are living his parents work. Therefore, every parent must give attention and affection to their children, this is one of the strategies and ways to encourage children to learn religion. Parents can provide direct role models for children on how to perform prayers, guide learning al-Qur'an, assist children in memorizing prayers and parents can rewards to children who show their good performance in the religious program. In addition, parents must always supervise their children in carrying out any activities, because that environment is very influential on the development of a child. If the environment is good, the child will develop well, and vice versa if the environment is not good then the child will follow bad things. Recently, the forms of religious attitudes of children is belief in heredity (customs), belief in awareness, religious indecision and disbelief in God.